Associative Nitrogen Fixation in Lowland Rice (Nepal Agriculture Research Journal, 2010)
Nitrogen (N), a most limiting nutrient, is the input required in the largest quantity for lowlandrice production. The concerns on N economy and efficiency and its impact on environment haverenewed interest in exploring alternative or supplementary N source for sustainable agriculture.Several studies have indicated the existence of significant rice genotypic differences in N2fixation stimulating traits (NFS). Rice genotypes with high NFS are desirable because they addN to the soil-water-plant system without additional farm inputs and reduce dependence onfertilizer. Large genotypic differences in percent N derived from air (% Ndfa) like 1.5% inAbang Basur, medium maturing genotype, to 21% in Oking Seroni, late maturing genotype,indicates potential of isolating genotypes with high NFS for sustainable agriculture. Theexogenous supply of nitrogenous fertilizer to lowland rice significantly inhibited N fixation butimproved plant growth. Where as phosphorous fertilizer did not affect atom % 15N excess and %Ndfa significantly but slight decrease in atom % 15N excess and increase in N2 fixation wasobserved. Inhibitory effect of exogenous supply of N fertilizer indicates limited potential ofassociative N2 fixation to significantly benefit agriculture. Farmers would have to withhold Nfertilizer from their rice crop in order to increase biological N2-fixation associated with rice. Ifthey do such practice the plants will be N deficient and might have a lower yield. However, thedevelopment of N fixation in response to a deficiency of available N may well be an integral partof the N cycle of natural ecosystem and low input farming system there by maintaining a Nbalance in the environment.Key words: Fertilizer; fixation; nitrogen; riceDOI: 10.3126/narj.v6i0.3373Nepal Agriculture Research Journal Vol.6 2005 pp.110-111